THE FUTURE OF EMPLOYMENT IN MANAUS, AMAZONAS: LEGAL CHALLENGES IN THE FACE OF ARTIFICIAL INTELLIGENCE AND LABOR AUTOMATION - Jerônimo Filho, Raimundo Simão; Cavalcante, Diego Rafael Cunha; Gonçalves, Dimas Melo; Soares, Rafaela Santos; Pereira, José Assis Vaz; Lopes, Caroline Moura (Seven Editora, 2026)
The advancement of artificial intelligence and automation has driven significant transformations in the world of work, directly impacting productive organization, employability, and labor legal relations. In this context, the present study aims to analyze the future of employment in Manaus, Amazonas, with emphasis on the legal challenges arising from the incorporation of these technologies into the productive environment, particularly within the Industrial Pole of Manaus. The research is characterized as a qualitative literature review, based on recent scientific studies and relevant institutional documents selected according to criteria of timeliness, thematic relevance, and academic rigor. The findings indicate that automation tends to replace repetitive tasks while increasing the demand for higher levels of professional qualification, which may intensify social inequalities if not accompanied by appropriate public policies. Furthermore, the study reveals that Labor Law faces limitations in regulating new forms of work organization mediated by technology, highlighting the need for normative updates. It is concluded that the future of employment in Manaus will depend on the articulation between technological innovation, legal regulation, and public policies, in order to ensure economic development with social inclusion and protection of workers’ rights.